Stability and stabilization of singular Markovian jump systems by dynamic event-triggered control strategy. (November 2020) - Guan, Chaoxu; Fei, Zhongyang; Feng, Zhiguang; Shi, Peng
Abstract: This paper investigates the problem of H ∞ control for continuous-time singular Markovian jump systems in the event-triggered framework. Different from the traditional event-triggered control systems, we introduce a dynamic event-triggered mechanism to monitor the data transmission from system plant to controller, which can lead to a smaller amount of data transmission and thus a higher efficiency of the communication resource. A positive lower bound on the inter-event intervals is proved to exist, which implies the exclusion of the Zeno behaviour. Based on this, sufficient conditions are obtained to ensure that the closed-loop system is stochastically admissible with an H ∞ disturbance attenuation. Then both the state feedback controller and the dynamic event-triggered mechanism are designed based on the analysis result. The dynamic event-triggered control is also extended to the system with network-induced delays due to the inevitability of time delay in practical transmission. Finally, two examples are provided to demonstrate the effectiveness and superiority of the proposed new design scheme.